МАКТАБГАЧА ТАЪЛИМ МУАССАСАЛАРИ ТАРБИЯЛАНУВЧИЛАРИНИ МИЛЛИЙ ҒОЯ РУҲИДА ТАРБИЯЛАШДА МЕДИАМАХСУЛОТЛАРИ ЎРНИ - Шерманова, Ф. (SCIENCE and SOCIETY, 2020)
The article examines the influence of electronic media on the formation of the outlook of the younger generation. Also the issues of media security were studied.
Keywords: modern technologies; social networks; media tools; Internet; media security; television; cartoon; mobile phone